Best squirrels trade a long life for an early reproduction - Descamps, Sébastien (The Royal Society, 2006)
Age at primiparity plays a crucial role in population dynamics and life-history evolution. Long-term data on female North American red squirrels were analysed to study the fitness consequences of delaying first reproduction. Early breeders were born earlier, had a higher breeding success and achieved a higher lifetime reproductive success than females who delayed their first reproduction, which suggests a higher quality of early breeders. However, early breeders had similar mass when tagged, and similar number of food caches available at one year of age as late breeders. Nevertheless, we found evidence of survival costs of early primiparity. Early breeders had a lower survival between one and two years of age than late breeders and a lower lifespan. Our study points out that two reproductive tactics co-occurred in this population: a tactic based on early maturity at the cost of a lower survival versus a tactic based on delayed maturity and long lifespan. High quality individuals express the most profitable tactic by breeding early whereas low quality individuals do the best of a bad job by delaying their first reproduction.